Domestic heating with compact combination hybrids (gas boiler and heat pump): A simple English stock model of different heating system scenarios. (March 2022) - Bennett, George; Watson, Stephen; Wilson, Grant; Oreszczyn, Tadj
The heat decarbonisation challenge remains substantial, competing low carbon solutions such as hydrogen and heat pumps (HPs) and the entrenched position of gas combination boilers create inertia in many markets. Hybrid appliances which can directly replace gas boilers may provide a low disruption, low-cost pathway to net zero in gas-reliant markets. Emerging compact combination (CoCo) hybrid heating appliances which combine a gas combi boiler and a small HP unit in one appliance have been modelled for the English housing stock across a range of different scenarios. CoCo hybrids offer sizeable energy demand reduction of up to 60% compared to current gas boilers, also reducing peak electrical demand by 10 GW compared to air source heat pumps. The control strategy for switching between HP and gas boiler is key in determining the scale of demand reduction. Modelling sensitivity to the HP size within CoCo hybrids showed that a 50% reduction in energy demand compared to gas boilers could be achieved with a standard 2.5 kW HP. A lack of clarity in regulation and policy incentives for hybrids exists. To drive innovation and performance improvement, product regulation for hybrids needs to be improved to support decarbonisation of heat with this promising technology. Practical Application: Convenient, low disruption heat decarbonisation technology is crucial to the speed of deployment necessary to achieve net zero. This article defines the size of HP necessary to achieve rapid low disruption impact and distinguishes the types of compact hybrid which can deliver the highest decarbonisation impact while minimising in house disruption and the electrical grid impact.